Single-cell RNA sequencing of circulating tumour cells in colorectal cancer - Sai Shyam Vasantharajan; Priyadarshana Ajithkumar; Kit Moloney-Geany; Hannah O’Neill; Euan J. Rodger; Sharon Pattison; Gregory Gimenez; Aniruddha Chatterjee (Molecular Biology Reports, 2026)
Background Circulating tumour cells (CTCs) are key mediators of metastasis and exhibit marked phenotypic plasticity driven by epithelial-to-mesenchymal transition (EMT). Traditional marker-based CTC isolation approaches rely on epithelial marker expression, which may fail to capture mesenchymal and hybrid CTC subpopulations. Hybrid CTCs remain poorly characterised in colorectal cancer (CRC). This study explored transcriptionally defined CTC subpopulations in CRC to provide insight into CTC heterogeneity. Methods Single-cell RNA sequencing (scRNA-seq) was performed on peripheral blood mononuclear cell (PBMC) fractions from four treatment-naive CRC patients (AJCC stages I–IV). Integrated analysis with healthy PBMC controls enabled immune cell exclusion and cell-type annotation. CTCs were identified using epithelial and mesenchymal transcriptional scores together with CD45 negativity. Differential expression, pathway enrichment, and pseudotime analyses were used to characterise epithelial, mesenchymal, and hybrid CTC states. Results Subpopulations of epithelial, mesenchymal, and hybrid cells were identified in one CRC patient. Hybrid CTCs exhibited distinct transcriptional features and enrichment of pathways related to RNA metabolism, protein trafficking, mitochondrial energy production, DNA repair, and cytoskeletal organisation. Trajectory inference suggested a continuous EMT spectrum, with hybrid CTCs occupying intermediate pseudotime states characterised by progressive loss of epithelial markers and acquisition of mesenchymal-associated features. Conclusion This study explored CTC heterogeneity in CRC using single-cell transcriptomics and identified epithelial, hybrid, and mesenchymal CTC states within the analysed sample. Hybrid CTCs exhibited distinct transcriptional features, providing preliminary insight into the transcriptional diversity of CRC CTCs. Further studies in larger cohorts are required to validate these findings and determine their clinical relevance.

Sea Lice ( Lepeophtheirus salmonis ) Harbour Putative Fish Pathogens: Insights From Illumina and Nanopore Sequencing - B. Klimesova; N. M. Ruane; R. Domingo‐Bretón; F. Moroni; F. Naya‐Català; J. Pérez‐Sánchez; K. O'Dwyer; O. Lyashevska; H. Rodger; A. Talbot (Journal of Fish Diseases, 2026)
Ectoparasites that penetrate host skin can act as biological or mechanical vectors for pathogens and, in some cases, serve as reservoirs. Crustacean ectoparasites of fish are potential vectors of pathogens, which is especially relevant for obligate pathogens (e.g., Aeromonas salmonicida ) with limited seawater survival. Sea lice ( Lepeophtheirus salmonis ), affecting Atlantic salmon, cause dermal damage and can facilitate secondary infections, resulting in economic losses. While the physical impact of sea lice is well known, their role in pathogen transmission is less clear. The gut bacterial microbiome of lice collected over four months from a salmon farm in Ireland was analysed using Illumina MiSeq and Oxford Nanopore Technologies (ONT) PromethION sequencing for comparison. Illumina and Nanopore sequencing identified 15 and 24 genera of known fish pathogens, respectively. Moreover, Nanopore data revealed up to 15 putative pathogenic species, including Tenacibaculum maritimum , T. dicentrarchi and Vibrio anguillarum , causative agents of tenacibaculosis and vibriosis. The results of this study provide a gut bacterial microbiome characterisation of L. salmonis in a commercial aquaculture setting and demonstrate the potential of sea lice to act as pathogen vectors or reservoirs. These findings have important implications for pathogen surveillance, management, and prevention strategies in salmon aquaculture.

The green gap framework: Understanding non and low use of urban greenspaces - Avril Johnstone; Rob Bushby; Ruth F Hunter; Sarah Rodgers; Catharine Ward Thompson; Andrew J Williams; Benedict W Wheeler; Richard Mitchell (Landscape and Urban Planning, 2026)

Investigation into the metabolomic effects of the non-canonical amino acid azetidine-2-carboxylic acid in neuroblastoma cells - Connor R. Phillips; Jake P. Violi; David S. Gertner; Joel R. Steele; David P. Bishop; Kenneth J. Rodgers (Food and Chemical Toxicology, 2026)

Towards implementation of precision medicine biomarkers in early detection and prognostication of prostate cancer - Angela Yee; Jim Smith; Rajiv Kumar; Akash Sali; Euan J. Rodger; Aniruddha Chatterjee (Cancer and Metastasis Reviews, 2026)
Prostate cancer is the second-highest cause of cancer-related incidence and the fifth-highest cause of cancer mortality in males. Prostate cancer is a heterogeneous disease with a wide spectrum of clinical behaviour, ranging from indolent to highly aggressive. Molecular approaches, such as genomic testing, can augment existing clinical risk stratifications and tailor management to the individual. Genomic tests that sample biopsy or surgical tissue can provide a molecular risk assessment and identify actionable therapy targets. Liquid biopsy, while still emerging, may provide a non-invasive alternative to tissue tests and enable longitudinal monitoring of tumour status. We first discuss the molecular landscape of prostate cancer, before providing a detailed overview of the molecular approaches available for early detection and prognostication. Furthermore, methodological considerations and barriers towards clinical implementation for these tests are discussed, highlighting areas of future research.

MyLogger: fast logging with HyLogger spectral mineralogy - J. M. Stromberg; C. Laukamp; E. J. Hill; A. Rodger (Australian Journal of Earth Sciences, 2026)

Preserving the gut microbiome: hydrogel-forming microneedle delivery of tetracycline reduces gut microbiome disruption compared to oral administration - Stephen A. Kelly; Li Zhao; Jonathan Nzakizwanayo; Aoife M. Rodgers; Thomas P. Thompson; Andrew J. Lee; Helen O. McCarthy; John W. McGrath; Rebecca J. Ingram; Brian V. Jones; Brendan F. Gilmore; Ryan F. Donnelly (Drug Delivery and Translational Research, 2026)
Antibiotics cause significant gut microbiome dysbiosis, particularly when administered orally. This contributes to antimicrobial resistance (AMR) and is associated with myriad health conditions. Novel drug delivery strategies that minimize gut exposure while maintaining therapeutic efficacy are urgently needed. This study aimed to evaluate whether a novel transdermal system could reduce gut microbiome disruption compared to oral delivery. Sprague-Dawley rats received a single tetracycline dose via oral gavage, IV injection, or hydrogel-forming microneedle patch. Faecal samples were collected longitudinally and analysed using 16 S rRNA gene sequencing. Oral tetracycline caused the greatest disruption to gut microbiota. Compared to the timepoint immediately prior to treatment (Day 5a), peak dysbiosis was observed at Day 7. The Firmicutes: Bacteroidetes ratio was significantly reduced following oral and IV tetracycline therapy, but not following microneedle administration. The most significant reductions in alpha and beta diversity at Day 7 were observed in the oral group. Differential abundance analysis showed oral treatment resulted in the highest number of depleted and enriched taxa. The microbiome-sparing effect of microneedle delivery was consistent across all analytical measures, offering a promising strategy to preserve host microbiome health. This minimally invasive approach represents a clinically viable alternative to oral and IV antibiotic administration.

A Review of Nonsteroidal Anti‐Inflammatory Drugs for Food‐Producing Animals With a Focus on Potential Applications for Farmed Finfish - Chloe J. English; Christine Huynh; William Roy; James W. Wynne; Hamish Rodger (Journal of Fish Diseases, 2026)
In finfish aquaculture, there are several inflammatory diseases impacting productivity and animal welfare, however there are limited options available to veterinarians to treat inflammation and pain in fish. Nonsteroidal anti‐inflammatory drugs (NSAIDs) are widely used in terrestrial animals raised for human consumption to treat a range of diseases and to manage pre‐ and postoperative pain as they offer anti‐inflammatory, antipyretic and analgesic properties. This review examines the use of NSAIDs in terrestrial food animals with the pharmacological and safety learnings to the possible use in aquaculture, specifically for oral administration of farmed salmonids. Across Norway, United Kingdom and Australia, which are salmon producing regions burdened by inflammatory disorders such as complex gill disease, seven NSAIDs are authorised for use in terrestrial food‐producing animals. The NSAIDs considered in this review have a good safety profile for users and the targeted terrestrial animal species, but more research is needed to develop safe and effective treatment regimens for farmed fish. Some NSAIDs have been shown to reduce pain sensitivity in fish but there is no published data demonstrating that they reduce inflammation. However, the targeted immune pathways of NSAIDs appear conserved between fish and terrestrial animals so it is highly likely that NSAIDs will have anti‐inflammatory effects in fish if they can be delivered effectively through in‐feed treatments. This review informs prescribing fish veterinarians and fish health professionals, as well as researchers, national licensing authorities and other stakeholders, to assist with consideration of the use and potential applications of the NSAIDs in finfish aquaculture.

Ecological risks and recent inputs of banned and current-use pesticides in surface water and sediment from Malawi's tobacco-growing region - Emmanuel Cishibanji; Rodgers Makwinja; Elias Chirwa; Benjamin N. Kondowe; John Kamanula; Christopher J. Curtis; Fabrice Muvundja; Bossissi Nkuba (Environmental Pollution, 2026)

Evaluating the evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards - Jason J. Kolbe; Jacob D. Ward; C. Mike Norris; John Rodgers; Sydney Wayne; Daniel A. Warner (Evolutionary Ecology, 2026)
Whether phenotypic plasticity facilitates adaptive evolution is a key question in evolutionary ecology. The discovery of limb-length plasticity in two Anolis lizard species led to hypotheses about its role in the Anolis radiation. Yet, whether limb plasticity is realized in nature and has adaptive significance is poorly understood. In this study, we combined a limb-length plasticity experiment, lab-based assays of hatchling behavior, and field-based measures of individual perch-diameter use of hatchling A. sagrei . We compared our findings to previous lab experiments and field studies to better understand the ecological conditions that might elicit limb plasticity and influence the adaptive potential of limb-length in Anolis lizards. Results from our lab experiment did not support limb-length plasticity. Significant limb-length differences due to plasticity were found in some previous experiments but not others. Intriguingly, repeated observations of individual hatchlings at night revealed consistent use of narrow-diameter perches for an island population. In contrast, individual diurnal perch-diameter use in adult A. sagrei was much less uniform. Little evidence exists for adaptive behavior or performance in hatchlings related to limb length and perch diameters. Several aspects of anole behavior and ecology, such as perch preferences and sleep-site use, influence perch-diameter use. Differences among populations in hindlimb length for Bahamian islands often exceed the average plastic response found in lab experiments. Evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards is currently mixed. A better understanding of how perch-diameter use results in biomechanical and developmental cues that influence limb growth is needed. The lack of clear support from lab and field studies urges caution when hypothesizing about the role of limb-length plasticity in the Anolis radiation.

Polystyrene nanoplastics disrupt ovarian development via cytoskeletal remodeling and epigenetic reprogramming particularly in granulosa cells - Mengyao Liu; Shenao Wang; Weijun Gao; Jian Zhang; Bin Zhang; Raymond J. Rodgers; Geng G. Tian; Xiaoyong Li; Ji Wu (Journal of Hazardous Materials, 2026)

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Insights from equitable governance assessments in conservation areas around the world - Naira Dehmel; Kate Schreckenberg; Phil Franks; Nikoleta Jones; Francesca Booker; Cosmas Lambini; Ruth Pinto; Alejandra Cely‐Gómez; Ishmael Chaukura; Donald Chilengwe Chikumbi; Phanith Chou; Ioli Christopoulou; et al. (Conservation Biology, 2026)
Global policy commitments to ensure that protected and conserved areas (PCAs) are equitably governed have increased interest in empirically assessing and analyzing social equity. Although numerous assessments have been conducted in individual PCAs, there is limited empirical insight into equity as a multidimensional concept beyond the site level. We investigated the distributional, procedural, and recognitional equity challenges associated with the governance of PCAs and determined whether the identified challenges differed according to governance type and actor group. We conducted a meta‐level analysis of equitable governance assessments conducted at 37 PCAs in 19 countries that form part of the new SAGE (Site‐level Assessment of Governance and Equity) database. SAGE is a participatory tool for site‐level actors to systematically discuss and assess equity dynamics at their PCAs. We found a large variation in assessment results across the sites. Mitigating the negative impacts of conservation on local communities was most often identified as the biggest challenge. In general, equity assessments tended to be slightly more positive for PCAs governed by and with Indigenous Peoples and local communities than those governed purely by government agencies. Evaluations of different actors often revealed substantial differences in opinion on specific governance issues. In particular, evaluations of PCA decision‐makers tended to be more positive than those of PCA users. As an early‐stage exploration of the growing SAGE database, our findings provide proof of concept that tools for assessing and improving PCA governance gain value from taking multidimensional approaches and need to consider different actors’ views. Although the growing SAGE database holds potential for further insights on how equity is perceived across governance types, ecosystems, and geographical regions, the primary objective of SAGE needs to remain understanding and advancing equity at the site level.

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Multifaceted Mesodiencephalic Triangles: Insights into Hypertrophic Olivary Degeneration and Oculopalatal Tremor Pathophysiology - Jorge C. Kattah; Kavya Moravineni; Eric Eggenberger; Cody Eggenberger; Aasef G. Shaikh; Rodger J. Elble (The Cerebellum, 2025)
Oculopalatal tremor is a rare neurological disorder characterized by rhythmic oscillations of ocular and palatal muscles. This phenomenon is commonly associated with hypertrophic degeneration of the inferior olive due to loss of GABAergic cerebello-olivary fibers. Oculopalatal tremor highlights the complex interplay between cerebellar, mesodiencephalic, and olivary networks. The principal, medial accessory, and dorsal accessory subnuclei of the inferior olive exhibit rhythmic subthreshold oscillations that are hypothesized to play an important role in oculopalatal tremor. However, delayed tremor onset and variability in hypertrophic olivary degeneration challenge the hypothesis of olivary oscillation as the principal cause of tremorogenesis. A plausible alternative hypothesis is that tremorogenic oscillation emerges from maladaptive cerebellar network plasticity in response to the loss of physiologic climbing fiber activity. The anatomy and physiology of the fastigiobulbar connections are compatible with the clinical characteristics of oculopalatal tremor syndrome, and clinicopathological correlations suggest that the fastigiobulbar pathway is necessary for oculopalatal tremor. Latent brainstem oscillators, released by cerebellar dysfunction, have been proposed but do not explain the anatomical distribution of oscillation. Advanced imaging and computational models have provided insights into possible mechanisms of oscillation but underscore the need for further studies, particularly in a suitable animal model, which does not exist.

P30-23 Boosting Early-Stage ADC Toxicity assessment through human in vitro cell models - B. Recolin; C. Rodger; J. Caruana Santiago; S. Randle; R. Foreman; K. Khan; M. Barbara; J. Kwon; R. Lucey; K. Pryde; M.-Y. Lee; S. Liu; et al. (Toxicology Letters, 2025)

Rankings of tuberculosis antibiotic treatment regimens are sensitive to spatial scale, detection limit, and initial host bacterial burden - Christian T. Michael; Maral Budak; Pauline Maiello; Kara Kracinovsky; Mark Rodgers; Jaime Tomko; Philana Ling Lin; JoAnne Flynn; Jennifer J. Linderman; Denise Kirschner (Journal of Theoretical Biology, 2025)

Quantitative post-earthquake building condition inference from exterior drift-sensitive nonstructural damage observations - Casey J. Rodgers; Nathaniel Levine; Billie F. Spencer (Engineering Structures, 2025)

The cyanobacterial toxins BMAA and 2,4-DAB perturb the l-serine biosynthesis pathway and induce systemic changes in energy metabolism in human neuroblastoma cells: A proteomic study - Lisa Pu; Joel R. Steele; Connor R. Phillips; Jake P. Violi; Kenneth J. Rodgers (Toxicology in Vitro, 2025)

Global landscape of space weather observations, research and operations - Mamoru Ishii; Joaquim E.R. Costa; Maria Kuznetsova; Mario M. Bisi; Amalia Meza; Astrid M. Veronig; Clezio Marcos Denardini; Christina Plainaki; Sergio Dasso; Manuela Temmer; María Graciela Molina; Jens Berdermann; et al. (Advances in Space Research, 2025)

Determinants of riverine migration success by Atlantic salmon ( Salmo salar ) smolts from rivers across the UK and Ireland - Jessica R. Rodger; Jemma Guthrie; Hannele M. Honkanen; Angus J. Lothian; Jessie Lilly; Marcus Walters; Richie Miller; Lorraine Hawkins; Al Reeve; Jamie Ribbens; Jim Henderson; Debbie Parke; et al. (Journal of Fish Biology, 2025)
There is some evidence that the river migration success of Atlantic salmon smolts, on their first migration to sea, varies both spatially and temporally. However, we have only a poor understanding of what may be driving this variation. In this study, we used acoustic telemetry to quantify the spatial and temporal variations in river migration success in Atlantic salmon smolts on their first migration to sea. In total 4120 Atlantic salmon smolts migrating through 22 rivers in Scotland, England, Ireland, and Northern Ireland over multiple years were included in the study. Individuals were defined as successful migrants if detected leaving the river to enter marine waters. The results show significant temporal (up to 4 years) and spatial (river) variations in migration success, with overall between‐river migration success varying from 3.4% to 97.0% and between years from 3.4% and 61.0%. Temporal variation in migration success was river specific, with some rivers being more temporally stable (exhibiting little variation between years) than others. Across all rivers and years, individual migration success was predicted positively by body condition and negatively by tag burden. The rate of migration success for a population (migration success standardized to a common river distance [proportion km −1 ]) was predicted by a number of environmental factors. The proportion of river catchment that comprised wetland and woodland positively predicted migration success, whereas the proportion of grassland and peatland in a catchment negatively predicted the rate of migration success. Although the mechanisms through which these effects may be operating were not directly examined in this study, we discuss some potential routes through which they may occur.

Inshore and offshore marine migration pathways of Atlantic salmon post‐smolts from multiple rivers in Scotland, England, Northern Ireland, and Ireland - Jessica R. Rodger; Jessie Lilly; Hannele M. Honkanen; Diego del Villar; Richard Kennedy; Niall Ó. Maoiléidigh; Patrick Boylan; Robert Rosell; David J. Morris; Ross O'Neill; Catherine Waters; Deirdre Cotter; et al. (Journal of Fish Biology, 2025)
The migratory behavior of Atlantic salmon ( Salmo salar ) post‐smolts in coastal waters is poorly understood. In this collaborative study, 1914 smolts, from 25 rivers, in four countries were tagged with acoustic transmitters during a single seasonal migration. In total, 1105 post‐smolts entered the marine study areas and 438 (39.6%) were detected on a network of 414 marine acoustic receivers and an autonomous underwater vehicle. Migration pathways (defined as the shortest distance between two detections) of up to 575 km and over 100 days at sea were described for all 25 populations. Post‐smolts from different rivers, as well as individuals from the same river, used different pathways in coastal waters. Although difficult to generalize to all rivers, at least during the year of this study, no tagged post‐smolts from rivers draining into the Irish Sea were detected entering the areas of sea between the Hebrides and mainland Scotland, which is associated with a high density of finfish aquaculture. An important outcome of this study is that a high proportion of post‐smolts crossed through multiple legislative jurisdictions and boundaries during their migration. This study provides the basis for spatially explicit assessment of the impact risk of coastal pressures on salmon during their first migration to sea.

Pinpointing regional unconformities in the Surat Basin, Australia, by statistical identification of neutron wireline log anomalies - C. Andrade; P. M. Vasconcelos; I. Rodger; S. Hörning; J. Esterle (Australian Journal of Earth Sciences, 2025)

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Psychological induction of interoceptive hunger cues and their effect on food desire - Richard J. Stevenson; Supreet Saluja; Jasmine Forsyth; Sophia Rodgers; Sophie Brasher; Vincent Ho; Heather M. Francis (Appetite, 2025)

The effect of downstream translocation on Atlantic salmon Salmo salar smolt outmigration success - Ruaidhri Forrester; Hannele M. Honkanen; Jessie Lilly; Amy Green; Jessica R. Rodger; Brian A. Shields; Philip Ramsden; J. Peter Koene; Melanie Fletcher; Colin W. Bean; Colin E. Adams (Journal of Fish Biology, 2025)
Trap and transport, the capture and subsequent translocation of fish during the freshwater phase of their migration, is becoming more common as a management intervention. Although the technique can be successful, it is costly and can have unintended effects on the fish being transported. This study investigates whether trap and transport can be used to increase the migration success of Atlantic salmon, Salmo salar , smolts in naturally flowing rivers. Seaward‐migrating S. salar ( n = 294) from two UK rivers were tracked using acoustic telemetric techniques. Outmigration success and timing were compared between non‐transported (released at the original in‐river capture site) and transported (released ca. 23 km downstream of the capture site) individuals. Downstream translocation increased the proportion of fish that successfully migrated to marine waters, and there was no indication that transport reduced post‐release survival. The post‐release migration speed of transported fish was slower than expected but this was likely a function of their advanced migration timing rather than an inhibition of their capacity to migrate. These results suggest that trap and transport can increase the outmigration success of S. salar smolts, but the earlier river exit dates of transported fish could negatively affect their survival at sea.

A comprehensive review of the proline mimic azetidine-2-carboxylic acid (A2C) - Kenneth J. Rodgers; James Kabalan; Connor R. Phillips (Toxicology, 2025)

A Ramsar site catchment undergoing major land use/land cover change: Scenarios from elephant marsh, Malawi - Rodgers Makwinja; Solomon G. Tesfamichael; Christopher J. Curtis (Remote Sensing Applications: Society and Environment, 2025)

Effects of macro vs. micro initialization and ocean initial-condition memory on the evolution of ensemble spread in the CESM2 large ensemble - Clara Deser; Who M. Kim; Robert C. J. Wills; Isla R. Simpson; Steve Yeager; Gokhan Danabasoglu; Keith Rodgers; Nan Rosenbloom (Climate Dynamics, 2025)
“Single Model initial-condition Large Ensembles” (SMILEs) conducted with Earth system models have transformed our ability to quantify internal climate variability and forced climate change at local and regional scales. An important consideration in their experimental design is the choice of initialization procedure as this influences the duration of initial-condition memory, with implications for interpreting the temporal evolution of both the ensemble-mean and ensemble-spread. Here we leverage the strategic design of the 100-member Community Earth System Model version 2 (CESM2) SMILE to investigate the dependence of ensemble spread on the method of initialization (micro- vs. macro- perturbations) and the effects of ocean initial-condition memory. We find that the evolution of ensemble spread in 10-year low-pass filtered data is relatively insensitive to the method of initialization beyond the second decade, with the notable exception of the tropical Indo-Pacific in the 4th decade, when macro-initialization significantly enhances ensemble spread, possibly as a result of a state-dependent response to major volcanic activity. Initial-condition memory associated with the chosen Atlantic Meridional Overturning Circulation (AMOC) states unfolds in two stages: First, in the North Atlantic lasting 4–5 decades, and subsequently, in the Indo-Pacific sector of the Southern Ocean appearing 35-years after initialization and lasting 3–4 decades. Known AMOC dynamics explain the first stage, but the role of AMOC and the mechanisms responsible for the delayed appearance of initial-condition memory in the Southern Ocean remain to be fully elucidated. Implications and recommendations for the design of future SMILEs are provided.

Bioaccumulation of β-methylamino-L-alanine (BMAA) by mussels exposed to the cyanobacteria Microcystis aeruginosa - Siobhan J. Peters; Simon M. Mitrovic; Kenneth J. Rodgers; David P. Bishop (Environmental Pollution, 2024)

Vulnerability of Ecosystem Services and Functions of Elephant Marsh, Malawi, to Land Use and Land Cover Change - Rodgers Makwinja; Christopher J. Curtis; Solomon G. Tesfamichael (Wetlands, 2024)
Elephant Marsh is among the Ramsar sites in Africa that exist in complex conditions where its ecosystem services and functions (ESFs) have changed in time and space. The past 24 years have seen it being exposed to various threats instigated by land use/land cover changes (LULCC). Assessing its vulnerabilities under LULCC scenarios is essential in understanding the trajectory of its ESFs and for framing practical policy responses. This paper characterizes the Elephant Marsh ESF threats (drivers), pressures, state, impact, and the effectiveness of responses. The integration of the Fuzzy Delph method and analytical hierarchy process ranked the threats. The vulnerability assessment results revealed that demographic indicators (0.92) posed the most critical threats, followed by socio-economic (0.84) and ecological indicators (0.76). LULCC that occurred in eight-year intervals (1998, 2006, 2014, and 2022) driven by human and environmental dynamics reduced Elephant Marsh ESFs evidenced by a decline in the cumulative resilience coefficient (0.57 to 0.15), and increase in extreme weather events cumulative coefficient (0.3 to 0.8), indicating vulnerability state. The most impacted ESFs include regulatory, supporting, provisioning, and cultural ESFs. The study further showed that the effort to restore these most vulnerable ESFs under the current changing climatic scenarios mismatched the demand for ecosystem provisioning services, evidenced by the expansion of cultivated and irrigated land at the expense of areas covered by water, marshes, and forests. This study recommends integrating climate change mitigation efforts and community resilience planning in the development and implementation of wetland policy, management plans, and restoration strategies.

P02-16 Modelling chemotherapy-induced peripheral neuropathy on-a-chip - X. Spijkers; G. Avramidou; W. Strijker; E. Nour; M. McFarlane; C. Rodger; J. Harper; L. Masterson; N. Wevers; S. Paternoster (Toxicology Letters, 2024)

Corrigendum to “Does the moon meddle with the lower ionosphere?” [J Atmos. Sol.-Terr. Phys. Volume 250, 2023, #106119] - Martin Friedrich; Mark Clilverd; Kerrache Fethia; Sushil Kumar; Craig J. Rodger (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Novel methods for monitoring low chlorophyll-a concentrations in the large, oligotrophic Lake Malawi/Nyasa/Niassa - Rodgers Makwinja; Yoshihiko Inagaki; Solomon G. Tesfamichael; Christopher J. Curtis (Journal of Environmental Management, 2024)

Vivaria housing conditions expose sex differences in brain oxidation, microglial activation, and immune system states in aged hAPOE4 mice - E. M. Reyes-Reyes; J. Brown; M. D. Trial; D. Chinnasamy; J. P. Wiegand; D. Bradford; R. D. Brinton; K. E. Rodgers (Experimental Brain Research, 2024)
Apolipoprotein E ε4 allele (APOE4) is the predominant genetic risk factor for late-onset Alzheimer’s disease (AD). APOE4 mouse models have provided advances in the understanding of disease pathogenesis, but unaccounted variables like rodent housing status may hinder translational outcomes. Non-sterile aspects like food and bedding can be major sources of changes in rodent microflora. Alterations in intestinal microbial ecology can cause mucosal barrier impairment and increase pro-inflammatory signals. The present study examined the role of sterile and non-sterile food and housing on redox indicators and the immune status of humanized- APOE4 knock-in mice (hAPOe4). hAPOE4 mice were housed under sterile conditions until 22 months of age, followed by the transfer of a cohort of mice to non-sterile housing for 2 months. At 24 months of age, the redox/immunologic status was evaluated by flow cytometry/ELISA. hAPOE4 females housed under non-sterile conditions exhibited: (1) higher neuronal and microglial oxygen radical production and (2) lower CD68 + microglia (brain) and CD8 + T cells (periphery) compared to sterile-housed mice. In contrast, hAPOE4 males in non-sterile housing exhibited: (1) higher MHCII + microglia and CD11b + CD4 + T cells (brain) and (2) higher CD11b + CD4 + T cells and levels of lipopolysaccharide-binding protein and inflammatory cytokines in the periphery relative to sterile-housed mice. This study demonstrated that sterile vs. non-sterile housing conditions are associated with the activation of redox and immune responses in the brain and periphery in a sex-dependent manner. Therefore, housing status may contribute to variable outcomes in both the brain and periphery.

Recovery of multireassortant bluetongue virus serotype 6 sequences from a mule deer (Odocoileus hemionus) and Dorset sheep (Ovis aries) in Colorado - Molly J. Carpenter; Case R. Rodgers; Mia K. Torchetti; Karen A. Fox; Mollie Burton; Tyler J. Sherman; Christie E. Mayo (Veterinary Microbiology, 2024)

Development of an open-source carbon footprint calculator of the UK craft brewing value chain - Alexander L. Bowler; Sarah Rodgers; Fanran Meng; Jon McKechnie; David J. Cook; Nicholas J. Watson (Journal of Cleaner Production, 2024)

Modulating signalling lifetime to optimise a prototypical animal opsin for optogenetic applications - Jessica Rodgers; Phillip Wright; Edward R. Ballister; Rebecca B. Hughes; Riccardo Storchi; Jonathan Wynne; Franck P. Martial; Robert J. Lucas (Pflügers Archiv - European Journal of Physiology, 2023)
Animal opsins are light activated G-protein-coupled receptors, capable of optogenetic control of G-protein signalling for research or therapeutic applications. Animal opsins offer excellent photosensitivity, but their temporal resolution can be limited by long photoresponse duration when expressed outside their native cellular environment. Here, we explore methods for addressing this limitation for a prototypical animal opsin (human rod opsin) in HEK293T cells. We find that the application of the canonical rhodopsin kinase (GRK1)/visual arrestin signal termination mechanism to this problem is complicated by a generalised suppressive effect of GRK1 expression. This attenuation can be overcome using phosphorylation-independent mutants of arrestin, especially when these are tethered to the opsin protein. We further show that point mutations targeting the Schiff base stability of the opsin can also reduce signalling lifetime. Finally, we apply one such mutation (E122Q) to improve the temporal fidelity of restored visual responses following ectopic opsin expression in the inner retina of a mouse model of retinal degeneration ( rd1 ). Our results reveal that these two strategies (targeting either arrestin binding or Schiff-base hydrolysis) can produce more time-delimited opsin signalling under heterologous expression and establish the potential of this approach to improve optogenetic performance.

OS03-09: Modelling Chemotherapy-Induced Peripheral Neuropathy on-a-chip - X. Spijkers; G. Avramidou; W. Strijker; M. McFarlane; C. Rodger; J. Harper; L. Masterson; N. Wevers (Toxicology Letters, 2023)

Bayesian and ultrasonic sensor aided multi-objective optimisation for sustainable clean-in-place processes - Alexander L. Bowler; Sarah Rodgers; David J. Cook; Nicholas J. Watson (Food and Bioproducts Processing, 2023)

Lower-ionosphere electron density and effective recombination coefficients from multi-instrument space observations and ground VLF measurements during solar flares - Vida Žigman; Marie Dominique; Davorka Grubor; Craig J. Rodger; Mark A. Clilverd (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Towards remote surveillance of marine pests: A comparison between remote operated vehicles and diver surveys - Leigh W. Tait; Jeremy Bulleid; Lily Pryor Rodgers; Kimberley Seaward; Louis Olsen; Chris Woods; Henry Lane; Graeme J. Inglis (Frontiers in Marine Science, 2023)
Early detection of marine invasive species is key for mitigating and managing their impacts to marine ecosystems and industries. Human divers are considered the gold standard tool for detecting marine invasive species, especially when dive teams are familiar with the local biodiversity. However, diver operations can be expensive and dangerous, and are not always practical. Remote operated vehicles (ROVs) can potentially overcome these limitations, but it is unclear how sensitive they are compared to trained divers for detecting pests. We assessed the sensitivity and efficiency of ROVs and divers for detecting marine non-indigenous species (NIS), including the potential for automated detection algorithms to reduce post-processing costs of ROV methods. We show that ROVs can detect comparable assemblages of invasive species as divers, but with lower detection rates (0.2 NIS min -1 ) than divers (0.5 NIS min -1 ) and covered less seafloor than divers per unit time. While small invertebrates (e.g., skeleton shrimp Caprella mutica ) were more easily detected by divers, the invasive goby Acentrogobius pflaumii was only detected by the ROV. We show that implementation of computer vision algorithms can provide accurate identification of larger biofouling organisms and reduce overall survey costs, yet the relative costs of ROV surveys remain almost twice that of diver surveys. We expect that as ROV technologies improve and investment in autonomous and semi-autonomous underwater vehicles increases, much of the current inefficiencies of ROVs will be mitigated, yet practitioners should be aware of limitations in taxonomic resolution and the strengths of specialist diver teams.

Inpatient GHB withdrawal management in an inner-city hospital in Sydney, Australia: a retrospective medical record review - Krista J. Siefried; Georgia Freeman; Darren M. Roberts; Rhiannon Lindsey; Craig Rodgers; Nadine Ezard; Jonathan Brett (Psychopharmacology, 2023)
Rationale Regular consumption of gamma-hydroxybutyrate (GHB) may result in a dependence syndrome that can lead to withdrawal symptoms. There are limited data on medications to manage GHB withdrawal. Objectives To examine characteristics associated with delirium and discharge against medical advice (DAMA), in the context of implementing a GHB withdrawal management protocol at an inner-city hospital in 2020. Methods We retrospectively reviewed records (01 January 2017–31 March 2021), and included admissions that were ≥ 18 years of age, admitted for GHB withdrawal, and with documented recent GHB use. Admissions were assessed for demographics, medications administered, features of delirium, ICU admission, and DAMA. Exploratory analyses were conducted to examine factors associated ( p < 0.2) with features of delirium and DAMA. Results We identified 135 admissions amongst 91 patients. Medications administered included diazepam (133 admissions, 98.5%), antipsychotics (olanzapine [70 admissions, 51.9%]), baclofen (114 admissions, 84%), and phenobarbital (8 admissions, 5.9%). Features of delirium were diagnosed in 21 (16%) admissions. Delirium was associated with higher daily GHB consumption prior to admission, while duration of GHB use, time from presentation to first dose of diazepam, and concomitant methamphetamine use were inversely associated with delirium. DAMA occurred amongst 41 (30%) admissions, and was associated with a longer time from presentation to first dose of baclofen, while being female and receiving a loading dose of diazepam were inversely associated. Conclusions This study adds to the literature in support of the safety and feasibility of diazepam and baclofen for the management of GHB withdrawal. Prospective, randomised trials are required.

Biological Sound Sources Drive Soundscape Characteristics of Two Australian Marine Parks - Jessica A. McCordic; Annamaria I. DeAngelis; Logan R. Kline; Candace McBride; Giverny G. Rodgers; Timothy J. Rowell; Jeremy Smith; Jenni A. Stanley; Allison Stokoe; Sofie M. Van Parijs (Frontiers in Marine Science, 2021)
Soundscapes represent an intrinsic aspect of a habitat which, particularly in protected areas, should be monitored and managed to mitigate human impacts. Soundscape ecology characterizes acoustic interactions within an environment, integrating biological, anthropogenic, climatological, and geological sound sources. Monitoring soundscapes in marine protected areas is particularly important due to the reliance of many marine species on sound for biological functions, including communication and reproduction. In this study we establish a baseline understanding of underwater soundscapes within two marine National Park Zones (NPZs) along the east coast of Australia: Cod Grounds Marine Park and an NPZ surrounding Pimpernel Rock within Solitary Islands Marine Park. In each of the NPZs, underwater recorders were deployed twice during the austral winter (33–35 days, 2018 and 60–69 days, 2019) and once during the austral summer (35–71 days, 2018–2019). We used the resulting acoustic recordings to determine hourly presence of anthropogenic and biological sounds between 20 Hz and 24 kHz and analyze their contributions to patterns of received sound levels. Sounds from vessels were recorded on most days throughout monitoring but were not found to influence long-term patterns of sound levels over their corresponding frequencies. Biological sources included dolphins, snapping shrimp, fish choruses, humpback whales, and dwarf minke whales. Dolphins, snapping shrimp, and fish choruses were present in all deployments. Median ambient sound levels showed a consistent diel pattern with increased levels resulting from crepuscular fish choruses combined with a higher intensity of snapping shrimp snaps during those times. Singing humpback whales strongly influenced the overall sound levels throughout the winter migration, while dwarf minke whales were consistently detected in the 2019 winter deployment but were only present in 2 h among the earlier deployments. Patterns of acoustic spectra were similar between the two NPZs, and patterns of soundscape measurements were observed to be driven by seasonal differences in biological contributions rather than anthropogenic sound sources, indicating that these NPZs are not yet heavily impacted by anthropogenic noise. These baseline measurements will prove invaluable in long-term monitoring of the biological health of NPZs.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Encapsulating Polyethyleneimine-DNA Nanoplexes into PEGylated Biodegradable Microparticles Increases Transgene Expression In Vitro and Reduces Inflammatory Responses In Vivo - Treniece L. Terry; Brittany E. Givens; Andrea Adamcakova-Dodd; Peter S. Thorne; Victor G. J. Rodgers; Aliasger K. Salem (AAPS PharmSciTech, 2021)

Epidemiology of marine gill diseases in Atlantic salmon ( Salmo salar ) aquaculture: a review - Annette S. Boerlage; Angela Ashby; Ana Herrero; Aaron Reeves; George J. Gunn; Hamish D. Rodger (Reviews in Aquaculture, 2020)
Gill disease of farmed Atlantic salmon ( Salmo salar ) in the marine environment has emerged as a significant problem for the salmon aquaculture industry. Different types of marine salmon gill disease reported include amoebic gill disease (AGD), parasitic gill disease, viral gill disease, bacterial gill disease, zooplankton (cnidarian nematocyst)‐associated gill disease, harmful algal gill disease and chemical/toxin‐associated gill disease. The term ‘multifactorial gill disease’ is used when multiple distinguishable types of disease (as opposed to an obvious single primary type) are present. When gill disease is non‐specific, it is referred to as ‘complex gill disease’ (CGD) or ‘complex gill disorder’. These two terms are often used interchangeably and are overlapping. The significance of many infectious and non‐infectious agents that may be associated with CGD is often unclear. In this review, we summarise aspects of the different types of gill disease that are relevant to the epidemiology of gill disease and of CGD in particular. We also tabulate simultaneously occurring putative pathogens to explore the multifactorial nature of gill disease.

Conspecific brood parasitism in an upland-nesting bird: cues parasites use to select a nest - Natalie J. Thimot; Rodger D. Titman; Kyle H. Elliott; Shawn R. Craik (Behavioral Ecology and Sociobiology, 2020)

Current Opinions and Consensus for Studying Tremor in Animal Models - Sheng-Han Kuo; Elan D. Louis; Phyllis L. Faust; Adrian Handforth; Su-youne Chang; Billur Avlar; Eric J. Lang; Ming-Kai Pan; Lauren N. Miterko; Amanda M. Brown; Roy V. Sillitoe; Collin J. Anderson; et al. (The Cerebellum, 2019)

Social-ecological change in the Omo-Turkana basin: A synthesis of current developments - Jennifer Hodbod; Edward G. J. Stevenson; Gregory Akall; Thomas Akuja; Ikal Angelei; Elias Alemu Bedasso; Lucie Buffavand; Samuel Derbyshire; Immo Eulenberger; Natasha Gownaris; Benedikt Kamski; Abdikadir Kurewa; et al. (Ambio, 2019)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Low-intensity repetitive transcranial magnetic stimulation over prefrontal cortex in an animal model alters activity in the auditory thalamus but does not affect behavioural measures of tinnitus - Wilhelmina H. A. M. Mulders; K. Leggett; V. Mendis; H. Tarawneh; J. K. Wong; J. Rodger (Experimental Brain Research, 2019)

Enhanced characterisation for the management of industrial steel processing by products: potential of sequential chemical extraction - Kiri J. Rodgers; Iain S. McLellan; Simon J. Cuthbert; Andrew S. Hursthouse (Environmental Monitoring and Assessment, 2019)

Tunable Properties of Poly-DL-Lactide-Monomethoxypolyethylene Glycol Porous Microparticles for Sustained Release of Polyethylenimine-DNA Polyplexes - Treniece L. Terry; Brittany E. Givens; Victor G. J. Rodgers; Aliasger K. Salem (AAPS PharmSciTech, 2019)

Investigation of co‐infections with pathogens associated with gill disease in Atlantic salmon during an amoebic gill disease outbreak - J K Downes; T Yatabe; M Marcos‐Lopez; H D Rodger; E MacCarthy; I O'Connor; E Collins; N M Ruane (Journal of Fish Diseases, 2018)
Gill diseases are a complex and multifactorial challenge for marine farmed Atlantic salmon. Co‐infections with putative pathogens are common on farms; however, there is a lack of knowledge in relation to the potential effect co‐infections may have on pathology. The objective of this study was to determine the prevalence and potential effects of Neoparamoeba perurans, Desmozoon lepeophtherii , Candidatus Branchiomonas cysticola, Tenacibaculum maritimum and salmon gill poxvirus ( SGPV ) during a longitudinal study on a marine Atlantic salmon farm. Real‐time PCR was used to determine the presence and sequential infection patterns of these pathogens on gill samples collected from stocking until harvest. A number of multilevel models were used to determine the effect of these putative pathogens on gill health (measured as gill histopathology score), while adjusting for the effect of water temperature and time since the last freshwater treatment. Results indicate that between 12 and 16 weeks post‐seawater transfer (wpst), colonization of the gills by all pathogens had commenced and by week 16 of marine production each of the pathogens had been detected. D. lepeophtherii and Candidatus B. cysticola were by far the most prevalent of the potential pathogens detected during this study. Detections of T. maritimum were found to be significantly correlated with temperature showing distinct seasonality. Salmon gill poxvirus was found to be highly sporadic and detected in the first sampling point, suggesting a carryover from the freshwater stage of production. Finally, the model results indicated no clear effect between any of the pathogens. Additionally, the models showed that the only variable which had a consistent effect on the histology score was N. perurans .

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Species and Genotype Effects of Bioenergy Crops on Root Production, Carbon and Nitrogen in Temperate Agricultural Soil - Andrew S. Gregory; Jennifer A. J. Dungait; Ian F. Shield; William J. Macalpine; Jennifer Cunniff; Mark Durenkamp; Rodger P. White; Adrian Joynes; Goetz M. Richter (BioEnergy Research, 2018)

Solar Photocatalysis Using Fixed-Film TiO2 for Microcystins from Colonial Microcystis aeruginosa - Ciera M. Kinley; Maas Hendrikse; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

In hot water: sustained ocean warming reduces survival of a low-latitude coral reef fish - G. G. Rodgers; J. M. Donelson; M. I. McCormick; P. L. Munday (Marine Biology, 2018)

Relationship among aqueous copper half-lives and responses of Pimephales promelas to a series of copper sulfate pentahydrate concentrations - Alyssa J. Calomeni; Ciera M. Kinley; Tyler D. Geer; Kyla J. Iwinski; Maas Hendrikse; John H. Rodgers (Ecotoxicology, 2018)

Cold tolerance and invasive potential of the redbay ambrosia beetle (Xyleborus glabratus) in the eastern United States - John P. Formby; John C. Rodgers; Frank H. Koch; Natraj Krishnan; Donald A. Duerr; John J. Riggins (Biological Invasions, 2018)

Microcystin-LR Degradation Following Copper-Based Algaecide Exposures - Ciera M. Kinley; Kyla J. Iwinski-Wood; Tyler D. Geer; Maas Hendrikse; Andrew D. McQueen; Alyssa J. Calomeni; Jenny Liang; Vanessa Friesen; Monique C. Simair; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Endogenous Sex Steroids Dampen Neuroinflammation and Improve Outcome of Traumatic Brain Injury in Mice - Amy C. Clevenger; Hoon Kim; Ernesto Salcedo; Joan C. Yonchek; Krista M. Rodgers; James E. Orfila; Robert M. Dietz; Nidia Quillinan; Richard J. Traystman; Paco S. Herson (Journal of Molecular Neuroscience, 2018)

Assessing the Combined Toxicity of BMAA and Its Isomers 2,4-DAB and AEG In Vitro Using Human Neuroblastoma Cells - Brendan J. Main; Kenneth J. Rodgers (Neurotoxicity Research, 2018)

Cyanobacterial Neurotoxins: Their Occurrence and Mechanisms of Toxicity - Kenneth J. Rodgers; Brendan J. Main; Kate Samardzic (Neurotoxicity Research, 2018)

Damage assessment by stiffness identification for a full-scale three-story steel moment resisting frame building subjected to a sequence of earthquake excitations - Cong Zhou; J. Geoffrey Chase; Geoffrey W. Rodgers; Chikara Iihoshi (Bulletin of Earthquake Engineering, 2017)

Characterization of Copper Algaecide (Copper Ethanolamine) Dissipation Rates Following Pulse Exposures - Alyssa J. Calomeni; Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Maas Hendrikse; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Advantages of melodic over rhythmic movement sonification in bimanual motor skill learning - J. F. Dyer; P. Stapleton; M. W. M. Rodger (Experimental Brain Research, 2017)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Reshaping structural hysteresis response with semi-active viscous damping - N. K. Hazaveh; G. W. Rodgers; J. G. Chase; S. Pampanin (Bulletin of Earthquake Engineering, 2017)

Thermosensitive period of sex determination in the coral-reef damselfish Acanthochromis polyacanthus and the implications of projected ocean warming - G. G. Rodgers; J. M. Donelson; P. L. Munday (Coral Reefs, 2017)

Predicting In Situ Responses of Taste- and Odor-Producing Algae in a Southeastern US Reservoir to a Sodium Carbonate Peroxyhydrate Algaecide Using a Laboratory Exposure-Response Model - Tyler D. Geer; Alyssa J. Calomeni; Ciera M. Kinley; Kyla J. Iwinski; John H. Rodgers (Water, Air, & Soil Pollution, 2017)

Differential modification of seawater carbonate chemistry by major coral reef benthic communities - Heather N. Page; Andreas J. Andersson; Paul L. Jokiel; Ku’ulei S. Rodgers; Mario Lebrato; Kiley Yeakel; Charlie Davidson; Sydney D’Angelo; Keisha D. Bahr (Coral Reefs, 2016)

Effects of Acid Volatile Sulfides (AVS) from Na2S-Amended Sediment on Hyalella azteca - Andrew D. McQueen; Ciera M. Kinley; Kyla J. Iwinski; Alyssa J. Calomeni; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Photocatalysis of a Commercial Naphthenic Acid in Water Using Fixed-Film TiO2 - Andrew D. McQueen; Ciera M. Kinley; Rebecca L. Kiekhaefer; Alyssa J. Calomeni; John H. Rodgers; James W. Castle (Water, Air, & Soil Pollution, 2016)

Sediment Copper Concentrations, In Situ Benthic Invertebrate Abundance, and Sediment Toxicity: Comparison of Treated and Untreated Coves in a Southern Reservoir - Kyla J. Iwinski; Andrew D. McQueen; Ciera M. Kinley; Alyssa J. Calomeni; Tyler D. Geer; John H. Rodgers (Water, Air, & Soil Pollution, 2016)

Genomic comparison of virulent and non‐virulent S treptococcus agalactiae in fish - C M J Delannoy; R N Zadoks; M Crumlish; D Rodgers; F A Lainson; H W Ferguson; J Turnbull; M C Fontaine (Journal of Fish Diseases, 2016)
Streptococcus agalactiae infections in fish are predominantly caused by beta‐haemolytic strains of clonal complex ( CC ) 7, notably its namesake sequence type ( ST ) 7, or by non‐haemolytic strains of CC 552, including the globally distributed ST 260. In contrast, CC 23, including its namesake ST 23, has been associated with a wide homeothermic and poikilothermic host range, but never with fish. The aim of this study was to determine whether ST 23 is virulent in fish and to identify genomic markers of fish adaptation of S . agalactiae . Intraperitoneal challenge of Nile tilapia, O reochromis niloticus ( L innaeus), showed that ST 260 is lethal at doses down to 10 2 cfu per fish, whereas ST 23 does not cause disease at 10 7 cfu per fish. Comparison of the genome sequence of ST 260 and ST 23 with those of strains derived from fish, cattle and humans revealed the presence of genomic elements that are unique to subpopulations of S . agalactiae that have the ability to infect fish ( CC 7 and CC 552). These loci occurred in clusters exhibiting typical signatures of mobile genetic elements. PCR ‐based screening of a collection of isolates from multiple host species confirmed the association of selected genes with fish‐derived strains. Several fish‐associated genes encode proteins that potentially provide fitness in the aquatic environment.

Long-Period Ground Motion in the Arabian Gulf from Earthquakes in the Zagros Mountains Thrust Belt - Arben Pitarka; Abdullah Al-Amri; Michael E. Pasyanos; Arthur J. Rodgers; Robert J. Mellors (Pure and Applied Geophysics, 2015)

Erratum to: The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - C. Stough; J. Lloyd; J. Clarke; L. A. Downey; C. W. Hutchison; T. Rodgers; P. J. Nathan (Psychopharmacology, 2015)

The effect of impedance to root growth on plant architecture in wheat - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Andrew L. Phillips; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Effect of combined radiation injury on cell death and inflammation in skin - Sachin S. Jadhav; Christopher J. Meeks; Nicholas M. Mordwinkin; Theresa B. Espinoza; Stan G. Louie; Gere S. diZerega; Kathleen E. Rodgers (Apoptosis, 2015)

Canopy interactions and physical stress gradients in subtidal communities - Scott Bennett; Thomas Wernberg; Thibaut de Bettignies; Gary A. Kendrick; Robert J. Anderson; John J. Bolton; Kirsten L. Rodgers; Nick T. Shears; Jean‐Charles Leclerc; Laurent Lévêque; Dominique Davoult; Hartvig C. Christie (Ecology Letters, 2015)
Species interactions are integral drivers of community structure and can change from competitive to facilitative with increasing environmental stress. In subtidal marine ecosystems, however, interactions along physical stress gradients have seldom been tested. We observed seaweed canopy interactions across depth and latitudinal gradients to test whether light and temperature stress structured interaction patterns. We also quantified interspecific and intraspecific interactions among nine subtidal canopy seaweed species across three continents to examine the general nature of interactions in subtidal systems under low consumer pressure. We reveal that positive and neutral interactions are widespread throughout global seaweed communities and the nature of interactions can change from competitive to facilitative with increasing light stress in shallow marine systems. These findings provide support for the stress gradient hypothesis within subtidal seaweed communities and highlight the importance of canopy interactions for the maintenance of subtidal marine habitats experiencing environmental stress.

Analysis of Algaecide Exposures: an Evaluation of the I3 − Method to Measure Sodium Carbonate Peroxyhydrate Algaecides - Ciera M. Kinley; John H. Rodgers; Kyla J. Iwinski; Andrew D. McQueen; Alyssa J. Calomeni (Water, Air, & Soil Pollution, 2015)

Global low-frequency motions in protein allostery: CAP as a model system - Philip D. Townsend; Thomas L. Rodgers; Ehmke Pohl; Mark R. Wilson; Tom C. B. McLeish; Martin J. Cann (Biophysical Reviews, 2015)

What Does Low-Intensity rTMS Do to the Cerebellum? - N. Morellini; S. Grehl; A. Tang; J. Rodger; J. Mariani; A. M. Lohof; R. M. Sherrard (The Cerebellum, 2015)

Wheat root growth responses to horizontal stratification of fertiliser in a water-limited environment - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

An outbreak of francisellosis in wild‐caught C eltic S ea A tlantic cod, G adus morhua L., juveniles reared in captivity - N M Ruane; M Bolton‐Warberg; H D Rodger; D J Colquhoun; M Geary; S J McCleary; K O'Halloran; K Maher; D O'Keeffe; L Mirimin; K Henshilwood; F Geoghegan; et al. (Journal of Fish Diseases, 2015)

Clinical cardiomyopathy syndrome in Atlantic salmon, Salmo salar L. - H D Rodger; S J McCleary; N M Ruane (Journal of Fish Diseases, 2014)

Behavioural profile of exendin-4/naltrexone dose combinations in male rats during tests of palatable food consumption - F. L. Wright; R. J. Rodgers (Psychopharmacology, 2014)

Natural attenuation of coal combustion waste in river sediments - James T. Markwiese; William J. Rogers; Neil E. Carriker; David I. Thal; Rock J. Vitale; Jacob G. Gruzalski; Erin E. Rodgers; Carol M. Babyak; Randall T. Ryti (Environmental Monitoring and Assessment, 2014)

Seismic Source Characteristics of Nuclear and Chemical Explosions in Granite from Hydrodynamic Simulations - Heming Xu; Arthur J. Rodgers; Ilya N. Lomov; Oleg Y. Vorobiev (Pure and Applied Geophysics, 2014)

On the behavioural specificity of hypophagia induced in male rats by mCPP, naltrexone, and their combination - F. L. Wright; R. J. Rodgers (Psychopharmacology, 2014)

Trait differences in response to chronic nicotine and nicotine withdrawal in rats - K. Z. Kolokotroni; R. J. Rodgers; A. A. Harrison (Psychopharmacology, 2014)

Quantitative Redox Biology: An Approach to Understand the Role of Reactive Species in Defining the Cellular Redox Environment - Garry R. Buettner; Brett A. Wagner; Victor G. J. Rodgers (Cell Biochemistry and Biophysics, 2013)

Differential characterization of emerging skin diseases of rainbow trout – a standardized approach to capturing disease characteristics and development of case definitions - B Oidtmann; S E LaPatra; D Verner‐Jeffreys; M Pond; E J Peeler; P A Noguera; D W Bruno; S St‐Hilaire; C B Schubiger; K Snekvik; M Crumlish; D M Green; et al. (Journal of Fish Diseases, 2013)
Farmed and wild salmonids are affected by a variety of skin conditions, some of which have significant economic and welfare implications. In many cases, the causes are not well understood, and one example is cold water strawberry disease of rainbow trout, also called red mark syndrome, which has been recorded in the UK since 2003. To date, there are no internationally agreed methods for describing these conditions, which has caused confusion for farmers and health professionals, who are often unclear as to whether they are dealing with a new or a previously described condition. This has resulted, inevitably, in delays to both accurate diagnosis and effective treatment regimes. Here, we provide a standardized methodology for the description of skin conditions of rainbow trout of uncertain aetiology. We demonstrate how the approach can be used to develop case definitions, using coldwater strawberry disease as an example.

Acute behavioural effects of bupropion and naltrexone, alone and in combination, in non-deprived male rats presented with palatable mash - F. L. Wright; R. J. Rodgers (Psychopharmacology, 2013)

Co‐Infection with Pseudomonas anguilliseptica and Delftia acidovorans in the European eel, Anguilla anguilla (L.): a case history of an illegally trafficked protected species - K B Andree; C J Rodgers; D Furones; E Gisbert (Journal of Fish Diseases, 2013)
Inspections by customs agents at Barcelona airport discovered 420 kg of contraband glass eels prepared for shipment to Hong Kong. After confiscation of these animals by police, they were transported to holding facilities to be maintained until after a judicial hearing. Upon arrival, they were separated into two groups and held under ambient flow‐through conditions in fresh water. During their captivity period, several peaks in mortality occurred and multiple bacterial strains were isolated from moribund animals. Sequencing of 16S rDNA was used to determine specific identity of the isolates. An initial isolation of Pseudomonas anguilliseptica was treated with oxytetracycline. A subsequent isolation of Delftia acidovorans proved resistant to oxytetracycline and was treated with gentamicin in combination with sulphadiazine–trimethoprim. Once the health condition of the animals was stabilized, they were partitioned into groups and subsequently released as part of a restocking effort for the species following the guidelines of Regulation (EC) 1100/2007 (Anon 2007). This represents the first record for both bacterial species in the host Anguilla anguilla in the Spanish Mediterranean.

Mixed-phenotype grouping: the interaction between oddity and crypsis - Gwendolen M. Rodgers; Helen Kimbell; Lesley J. Morrell (Oecologia, 2013)

Low dose naloxone attenuates the pruritic but not anorectic response to rimonabant in male rats - F. L. Wright; R. J. Rodgers (Psychopharmacology, 2013)

A modified Latent Class Model assessment of human papillomavirus-based screening tests for cervical lesions in women with atypical glandular cells: a Gynecologic Oncology Group study - Randy L. Carter; Le Kang; Kathleen M. Darcy; James Kauderer; Shu-Yuan Liao; William H. Rodgers; Joan L. Walker; Heather A. Lankes; S. Terence Dunn; Eric J. Stanbridge (Cancer Causes & Control, 2012)

Development of a novel histopathological gill scoring protocol for assessment of gill health during a longitudinal study in marine-farmed Atlantic salmon (Salmo salar) - Susan O. Mitchell; Emily J. Baxter; Celia Holland; Hamish D. Rodger (Aquaculture International, 2012)

Development of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum and its application to field samples - E Fringuelli; P D Savage; A Gordon; E J Baxter; H D Rodger; D A Graham (Journal of Fish Diseases, 2012)
The development and the application of a quantitative real‐time PCR for the detection of Tenacibaculum maritimum are described. A set of primers and probe was designed to amplify a 155‐bp fragment specific to the T. maritimum 16S rRNA gene. The test was shown to be very sensitive, able to detect as little as 4.8 DNA copies number μL −1 . In addition, the assay was found to have a high degree of repeatability and reproducibility, with a linear dynamic range ( R 2 = 0.999) extending over 6 log 10 dilutions and a high efficiency (100%). The assay was applied to DNA samples extracted from 48 formalin‐fixed paraffin‐embedded (FFPE) Atlantic salmon, Salmo salar, gill tissues showing varying degrees of gill pathology (scored 0–3) and from 26 jellyfish samples belonging to the species Phialella quadrata and Muggiaea atlantica . For each sample, the bacterial load was normalised against the level of the salmonid elongation factor alpha 1 (ELF) detected by a second real‐time PCR using previously published primers and probe. Tenacibaculum maritimum DNA was detected in 89% of the blocks with no signs of gill disease as well as in 95% of the blocks with mild‐to‐severe gill pathology. Association between bacterial load and gill pathology severity was investigated. T. maritimum DNA was detected at low level in four of the 26 jellyfish tested.

Responses of Lyngbya wollei to Exposures of Copper-Based Algaecides: The Critical Burden Concept - W. M. Bishop; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 2012)

Effects of chronic nicotine, nicotine withdrawal and subsequent nicotine challenges on behavioural inhibition in rats - K. Z. Kolokotroni; R. J. Rodgers; A. A. Harrison (Psychopharmacology, 2012)

Acute nicotine increases both impulsive choice and behavioural disinhibition in rats - Katerina Zoe Kolokotroni; Robert J. Rodgers; Amanda A. Harrison (Psychopharmacology, 2011)

A comparative analysis of sperm storage and mating strategies in five species of brachyuran crabs - Paula J. Rodgers; Marjorie L. Reaka; Anson H. Hines (Marine Biology, 2011)

Versican induces a pro-metastatic ovarian cancer cell behavior which can be inhibited by small hyaluronan oligosaccharides - Miranda P. Ween; Katja Hummitzsch; Raymond J. Rodgers; Martin K. Oehler; Carmela Ricciardelli (Clinical & Experimental Metastasis, 2011)

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

Dynamics of extracellular matrix in ovarian follicles and corpora lutea of mice - Helen F. Irving-Rodgers; Katja Hummitzsch; Lydia S. Murdiyarso; Wendy M. Bonner; Yoshikazu Sado; Yoshifumi Ninomiya; John R. Couchman; Lydia M. Sorokin; Raymond J. Rodgers (Cell and Tissue Research, 2010)

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Source mechanisms of the June 2004 Tabuk earthquake sequence, Eastern Red Sea margin, Kingdom of Saudi Arabia - K. S. Aldamegh; K. M. Abou Elenean; H. M. Hussein; A. J. Rodgers (Journal of Seismology, 2009)

Ruthenium polypyridyl complexes and their modes of interaction with DNA: Is there a correlation between these interactions and the antitumor activity of the compounds? - Eva Corral; Anna C. G. Hotze; Hans den Dulk; Anna Leczkowska; Alison Rodger; Michael J. Hannon; Jan Reedijk (JBIC Journal of Biological Inorganic Chemistry, 2009)

Phylogenetic analyses and molecular epidemiology of European salmonid alphaviruses (SAV) based on partial E2 and nsP3 gene nucleotide sequences - E Fringuelli; H M Rowley; J C Wilson; R Hunter; H Rodger; D A Graham (Journal of Fish Diseases, 2008)
Sequence data were generated for portions of the E2 and nsP3 genes of 48 salmonid alphaviruses from farmed Atlantic salmon (AS), Salmo salar L . , and rainbow trout (RT), Oncorhynchus mykiss (Walbaum), in marine and freshwater environments, respectively, from the Republic of Ireland, Northern Ireland, England, Scotland, Norway, France, Italy and Spain between 1991 and 2007. Based on these sequences, and those of six previously published reference strains, phylogenetic trees were constructed using the parsimony method. Trees generated with both gene segments were similar. Clades corresponding to the three previously recognized subtypes were generated and in addition, two further new clades of viruses were identified. A single further strain (F96‐1045) was found to be distinct from all of the other strains in the study. The percentage of nucleotide divergence within clades was generally low (0–4.8% for E2, 0–6.6% for nsP3). Interclade divergence tended to be higher (3.4–19.7% for E2, 6.5–28.1% for nsP3). Based on these results and using current SAV terminology, the two new clades and F96‐1045 were termed SAV subtypes 4, 5 and 6, respectively. SAV4 contained AS strains from Ireland and Scotland, while SAV5 contained only Scottish AS strains. Recently identified SAV strains from RT in Italy and Spain were shown to belong to SAV2. In addition, marine AS strains belonging to SAV2 were identified for the first time. Analysis of the origin of several clusters of strains with identical E2 and nsP3 sequences strongly support horizontal transmission of virus between farms and aquaculture companies. Evidence in support of vertical transmission was not found.

Ocean acidification and calcifying reef organisms: a mesocosm investigation - P. L. Jokiel; K. S. Rodgers; I. B. Kuffner; A. J. Andersson; E. F. Cox; F. T. Mackenzie (Coral Reefs, 2008)

Improving the level of seismic hazard parameters in Saudi Arabia using earthquake location - Abdullah M. Al-Amri; Arthur J. Rodgers; Tariq A. Al-Khalifah (Arabian Journal of Geosciences, 2008)

Grooming, scratching and feeding: role of response competition in acute anorectic response to rimonabant in male rats - A. J. Tallett; J. E. Blundell; R. J. Rodgers (Psychopharmacology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Actin plays a crucial role in the phagocytosis and biological response to respirable quartz particles in macrophages - Petra Haberzettl; Rodger Duffin; Ursula Krämer; Doris Höhr; Roel P. F. Schins; Paul J. A. Borm; Catrin Albrecht (Archives of Toxicology, 2007)

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)

Characterization of Aeromonas Virulence Using an Immunocompromised Mouse Model - Dennis J. Lye; Mark R. Rodgers; Gerard Stelma; Stephen J. Vesper; Samuel L. Hayes (Current Microbiology, 2007)

Atypical anxiolytic-like response to naloxone in benzodiazepine-resistant 129S2/SvHsd mice: role of opioid receptor subtypes - R. J. Rodgers; R. Augar; N. Berryman; C. J. Hansom; M. L. O’Mahony; R. M. Palmer; A. Stevens; A. J. Tallett (Psychopharmacology, 2006)

Interannual-to-decadal variability of North Atlantic air-sea CO 2 fluxes - S. Raynaud; J. C. Orr; O. Aumont; K. B. Rodgers; P. Yiou (Ocean Science, 2006)
The magnitude of the interannual variability of North Atlantic air-sea CO2 fluxes remains uncertain. Interannual extremes simulated by atmospheric inverse approaches are typically about ±0.3 Pg C yr−1, whereas those from ocean models are less than ±0.1 Pg C yr−1. Thus variability in the North Atlantic is either about 60% or less than 20% of the global variability of about ±0.5 Pg C yr−1 (as estimated by both approaches). Here we explore spatiotemporal variability within the North Atlantic basin of one ocean model in order to more fully describe potential counteracting trends in different regions that may explain why basin-wide variability is small relative to global-scale variability. Typical atmospheric inverse approaches separate the North Atlantic into at most a few regions and thus cannot properly simulate such counteracting effects. For this study, two simulations were made with a biogeochemical model coupled to a global ocean general circulation model (OGCM), which itself was forced by 55-year NCEP reanalysis fields. In the first simulation, atmospheric CO2 was maintained at the preindustrial level (278 ppmv); in the second simulation, atmospheric CO2 followed the observed increase. Simulated air-sea CO2 fluxes and associated variables were then analysed with a statistical tool known as multichannel singular spectrum analysis (MSSA). We found that the subtropical gyre is not the largest contributor to the overall, basin-wide variability, in contrast to previous suggestions. The subpolar gyre and the inter-gyre region (the transition area between subpolar and subtropical gyres) also contribute with multipolar anomalies at multiple frequencies: these tend to cancel one another in terms of the basin-wide air-sea CO2 flux. We found a strong correlation between the air-sea CO2 fluxes and the North Atlantic Oscillation (NAO), but only if one takes into account time lags as does MSSA (maximum r=0.64 for lags between 1 and 3 years). The effect of increasing atmospheric CO2 (the anthropogenic perturbation) on total variability was negligible at interannual time scales, whereas at the decadal (13-year) time scale, it increased variability by 30%.

Feeding responses to selected alkaloids by gypsy moth larvae, Lymantria dispar (L.) - Vonnie D. C. Shields; Erin J. Rodgers; Nicole S. Arnold; Denise Williams (The Science of Nature, 2006)

Cellular uptake and cytotoxic potential of respirable bentonite particles with different quartz contents and chemical modifications in human lung fibroblasts - Stefan Geh; Raif Yücel; Rodger Duffin; Catrin Albrecht; Paul J. A. Borm; Lorenz Armbruster; Monika Raulf-Heimsoth; Thomas Brüning; Eik Hoffmann; Albert W. Rettenmeier; Elke Dopp (Archives of Toxicology, 2006)

Ab initio elasticity of FeS2 pyrite from 0 to 135 GPa - Y. Le Page; J. R. Rodgers (Physics and Chemistry of Minerals, 2005)

Extracellular matrix in ovarian follicular development and disease - Helen F. Irving-Rodgers; Raymond J. Rodgers (Cell and Tissue Research, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

The Responses of Selected Terrestrial Plants to Short (<12 days) and Long Term (2, 4 and 6 Weeks) Hexahydro-1,3,5-Trinitro-1,3,5-Triazine (RDX) Exposure. Part I: Growth and Developmental Effects - Linda E. Winfield; John H. Rodger; Stephen J. D'surney (Ecotoxicology, 2004)

Spatial variation in soil compaction, and the burrowing activity of the earthworm Aporrectodea caliginosa - Robert J. Stovold; W. Richard Whalley; Peter J. Harris; Rodger P. White (Biology and Fertility of Soils, 2004)

Nucleation of calcium oxalate crystals on an imprinted polymer surface from pure aqueous solution and urine - Timothy J. Egan; Allen L Rodgers; Tewolde Siele (JBIC Journal of Biological Inorganic Chemistry, 2004)

The reality of psychomotor problems, and the possibility of Parkinson?s disorder, in some recreational ecstasy/MDMA users: a rejoinder to Sumnall et al. (2003) - A. C. Parrott; J. Rodgers; T. Buchanan; A. B. Scholey; T. Heffernan; J. Ling (Psychopharmacology, 2004)

Interaction between a DNA oligonucleotide and a dinuclear iron(II) supramolecular cylinder; an NMR and molecular dynamics study - Erlend Moldrheim; Michael J. Hannon; Isabelle Meistermann; Alison Rodger; Einar Sletten (JBIC Journal of Biological Inorganic Chemistry, 2002)

Algicidal Effectiveness of Clearigate, Cutrine-Plus, and Copper Sulfate and Margins of Safety Associated with Their Use - C. L. Murray-Gulde; J. E. Heatley; A. L. Schwartzman; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 2002)

Seismic Discrimination of the May 11, 1998 Indian Nuclear Test with Short-period Regional Data from Station NIL (Nilore, Pakistan) - A. J. Rodgers; W. R. Walter (Pure and Applied Geophysics, 2002)

A maize bacterial artificial chromosome (BAC) library from the European flint inbred line F2 - D. M. O’Sullivan; P. J. Ripoll; M. Rodgers; K. J. Edwards (Theoretical and Applied Genetics, 2001)

The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - Stough C.; Nathan P.; Lloyd J.; Clarke J.; Hutchison C.; Downey L.; Rodgers T. (Psychopharmacology, 2001)

Early ontogeny of coal grunter from hormone‐induced spawnings and laboratory‐reared embryos and larvae - P. G. Close; C. G. Barlow; L. J. Rodgers (Journal of Fish Biology, 2001)
Spawning of coal grunter Hephaestus carbo was successfully induced using doses of human chorionic gonadotrophin (hCG) between 500 and 3000 IU kg (body weight) −1 . Water hardened eggs are telolecithal, amber in colour, spherical, transparent, demersal and slightly adhesive with a single large oil droplet and perivitelline space 47% of total egg volume. Cleavage begins 10–15 min after fertilization. Epiboly begins 6h after fertilization and continues for 4 h. Invagination of the neural tube is apparent 11·5 h after fertilization, followed by progressive organogenesis up to hatching 60–80 h after fertilization. An invagination in the yolk, consistent in shape, position and time of appearance among embryos spawned from numerous brood stock pairs, was visible in all fertilized eggs between neurulation (11‐5 h) and early organogenesis (20 h). The functional significance of this yolk invagination is unknown. Newly‐hatched larvae (4·2 mm L T ) are elongate and possess well developed eyes, a functional mouth, and a large yolk sac. Yolk is fully resorbed and first feeding occurs at 6 days posthatching. The sequence of fin formation is caudal, second dorsal and anal, first dorsal, pectoral and pelvic. The prefiexion larval stage lasts for c. 8 days and flexion of the notochord is complete within a further 8–9 days. Squamation commences at 30 days posthatching and transition to the juvenile life stage is complete by 35–40 days posthatching.

Toxicity and Bioavailability of Copper Herbicides (Clearigate, Cutrine-Plus, and Copper Sulfate) to Freshwater Animals - B. J. Mastin; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 2000)

Cognitive performance amongst recreational users of "ecstasy" - J. Rodgers (Psychopharmacology, 2000)

Effects of a Homologous Series of Linear Alcohol Ethoxylate Surfactants on Fathead Minnow Early Life Stages - R. E. Lizotte Jr.; D. C. L. Wong; P. B. Dorn; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Characterization of magnetite particles in shocked quartz by means of electron- and magnetic force microscopy: Vredefort, South Africa - Marthinus Cloete; Rodger J. Hart; Herbert K. Schmid; Martyn Drury; Chris M. Demanet; K. Vijaya Sankar (Contributions to Mineralogy and Petrology, 1999)

Behavioural profiles in the mouse defence test battery suggest anxiolytic potential of 5-HT 1A receptor antagonists - G. Griebel; R. John Rodgers; Ghislaine Perrault; David J. Sanger (Psychopharmacology, 1999)

Ultrastructure and composition of Call-Exner bodies in bovine follicles - I. L. van Wezel; H.F. Irving-Rodgers; Y. Sado; Y. Ninomiya; R. J. Rodgers (Cell and Tissue Research, 1999)

Copper Bioavailability in Steilacoom Lake Sediments - D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Comparative effects of novel 5-HT 1A receptor ligands, LY293284, LY315712 and LY297996, on plus-maze anxiety in mice - B.-J. Cao; R. J. Rodgers (Psychopharmacology, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Devensian organic interstadial deposits and ice sheet extent in Buchan, Scotland - Graeme Whittington; Rodger E. Connell; G. Russell Coope; Kevin J. Edwards; Adrian M. Hall; Peter D. Hulme; Jack Jarvis (Journal of Quaternary Science, 1998)

Characterization of CHO-K1 cells stably expressing PDE-IV enzymes - D. J. Pon; M. Plant; J. Tkach; L. Boulet; E. Muise; R. A. Allen; I. W. Rodger (Cell Biochemistry and Biophysics, 1998)

Comparative Toxicity of Chlordane, Chlorpyrifos, and Aldicarb to Four Aquatic Testing Organisms - M. T. Moore; D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr.; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 1998)

Differential effects of chlordiazepoxide on aggressive behavior in male mice: the influence of social factors - P. F. Ferrari; S. Parmigiani; R. J. Rodgers; P. Palanza (Psychopharmacology, 1997)

Experimental Factors That May Affect Toxicity of Cadmium to Freshwater Organisms - B. C. Suedel; J. H. Rodgers Jr.; E. Deaver (Archives of Environmental Contamination and Toxicology, 1997)

Comparative Aqueous Toxicity of Silver Compounds: Laboratory Studies with Freshwater Species - J. H. Rodgers, Jr.; E. Deaver; B. C. Suedel; P. L. Rogers (Bulletin of Environmental Contamination and Toxicology, 1997)

Anxiolytic-like profile of p -MPPI, a novel 5HT 1A receptor antagonist, in the murine elevated plus-maze - B.-J. Cao; R. J. Rodgers (Psychopharmacology, 1997)

Formulated sediment as a reference and dilution sediment in definitive toxicity tests - B. C. Suedel; E. Deaver; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 1996)

Experimental factors that may affect toxicity of aqueous and sediment-bound copper to freshwater organisms - B. C. Suedel; E. Deaver; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 1996)

Formulated Sediment as a Reference and Dilution Sediment in Definitive Toxicity Tests - B. C. Suedel; E. Deaver; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 1996)

Experimental Factors That May Affect Toxicity of Aqueous and Sediment-Bound Copper to Freshwater Organisms - B. C. Suedel; E. Deaver; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 1996)

Multiple drug resistance inAerobacter aerogenes - P. G. Bolion; A. C. R. Dean; P. J. Rodgers (Antonie van Leeuwenhoek, 1967)